DETERMINING THE FITNESS LEVEL OF MIDDLE SCHOOL STUDENTS BY APPLYING A BATTERY OF SPECIFIC TESTS (GYMNASIUM, 2017)
In this brief presentation we propose to differentiate the concept of "fitness" as a component of the human condition indicator of health and identify categories of values and its features. The idea that if we apply a more complex battery of tests investigating all basic motor skills, driving qualities that are measurable in higher weight than the other components of the educational process (knowledge, skills, abilities), we can obtain ample information to the extent we ensure the quality of the process and the level reached by students in biomedical plan. Research group consisted of schoolchildren, so we organized study of the morph-functional development of students with a total of 100 students, differences by gender (boys and girls separately). As a final conclusion it requires constant attention to be paid to evaluating the process of physical education and measuring its orientation in order to obtain conclusive and complete data on somatic and sensory capacities - functional and driving student, allowing an assessment flexible level of the school population.